Clustering of Companies Based on Sustainability Performance using ESG Materiality Approach: Evidence from Indonesia - Saraswati, Erwin; Ghofar, Abdul; Atmini, Sari; Dewi, Ayu Aryista (International Journal of Energy Economics and Policy, 2024)
The framework for environmental, social, and governance (ESG) disclosure has become crucial throughout the world. Globally, various ESG reporting frameworks have emerged, but there are still few companies in Indonesia that are involved in ESG. This research aims to develop an ESG performance assessment instrument based on material aspects of sustainability for all industries in Indonesia. The data was obtained by extracting 472 corporate sustainability reports in Indonesia during 2021 and ESG indicators were determined through focus group discussions and inter-rater reliability tests. The ESG performance assessment in this study adopted the methodology of the Refinitiv Institute and the ESG indicator weights were modified according to the new ESG indicators. A total of 65 ESG indicators were analyzed and these showed that the majority of companies in Indonesia have relatively satisfactory ESG performance and a moderate level of transparency in reporting important ESG data to the public. Cluster analysis with the K-means algorithm shows that each company needs to improve performance on at least one ESG pillar. The results of this research support the initiatives that have been taken by global regulators and stock exchanges to require companies to disclose ESG information in the future.